Business Growth Analysis for Micro and Small Enterprises, Post-Financing of Mudharaba by BMT Khalifah Amanah in Medan Tembung Sub-district - Dwi Saraswati (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Micro and Small Enterprises (MSEs) are the primary drivers of the economic sector in trade and services. Generally, the obstacle that is often the spotlight of Micro and Small Enterprises is the classic problem of capital. The tendency of micro and small entrepreneurs to run a business is always focused on the lack of working capital. The purpose of this study is to analyze the differences and business growth of Micro and Small Enterprises past and post-financing which includes working capital, Business turnover, and profit. The object of this research is Micro, and Small Enterprises which is a member of BMT Kalifah Amanah with sample amounted to 95. The types of data collected are primary and secondary data. Methods of data analysis in this study include multiple linear regression analysis, and t-test. The research findings indicate that there is an increase in the amount of venture capital, Business turnover and profit from Micro and Small Enterprises (MSEs).